(untitled) (International Journal of Environmental Sciences, 2023)
A broad industry consensus has formed in the aquaculture sector that the core factors influencing the growth and production performance of Pacific white shrimp (Litopenaeus vannamei) are stocking density and salinity. Meanwhile, water quality parameters including pH, dissolved oxygen, ammonia nitrogen, and temperature are also key conditions for maintaining a suitable environment in aquaculture ponds that supports shrimp growth and survival. To further clarify the actual impacts of these two core factors, this study set up four experimental pond groups with different combinations of salinity and stocking density during the second crop of 2018 in Krishna District, Andhra Pradesh, India. The four groups are: low salinity and low stocking density, low salinity and high stocking density, high salinity and low stocking density, and high salinity and high stocking density. Throughout the full breeding period, the growth rate of Litopenaeus vannamei was continuously monitored, and the average monitored values of all core water quality parameters (including pH, dissolved oxygen, ammonia nitrogen, and temperature) for the four pond groups were synchronously recorded and collated. Based on analysis and inference of all experimental data, this study reached the following core conclusion: stocking density is negatively correlated with the growth and production capacity of Litopenaeus vannamei. Under both low-salinity and high-salinity conditions, the production performance of low stocking density groups outperforms that of high stocking density groups, and high-density farming reduces the overall aquaculture production capacity.